2014
DOI: 10.1038/ismej.2014.238
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for extensive gene flow and Thermotoga subpopulations in subsurface and marine environments

Abstract: Oil reservoirs represent a nutrient-rich ecological niche of the deep biosphere. Although most oil reservoirs are occupied by microbial populations, when and how the microbes colonized these environments remains unanswered. To address this question, we compared 11 genomes of Thermotoga maritima-like hyperthermophilic bacteria from two environment types: subsurface oil reservoirs in the North Sea and Japan, and marine sites located in the Kuril Islands, Italy and the Azores. We complemented our genomes with The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 64 publications
0
48
0
Order By: Relevance
“…The percentage of genes in the Methanohalophilus core genome is much lower than Thermotoga (>90% core genes, n = 11) , a bacterium that spans surface ( n = 4) and deeper ( n = 7) ecosystems (Nesbø et al, ). In fact, the relative abundance of genes in the core genome for Methanohalophilus is closer to Prochlorococcus , a highly abundant marine photosynthetic bacterial genus, with a core genome of about 50% ( n = 49) (Biller et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of genes in the Methanohalophilus core genome is much lower than Thermotoga (>90% core genes, n = 11) , a bacterium that spans surface ( n = 4) and deeper ( n = 7) ecosystems (Nesbø et al, ). In fact, the relative abundance of genes in the core genome for Methanohalophilus is closer to Prochlorococcus , a highly abundant marine photosynthetic bacterial genus, with a core genome of about 50% ( n = 49) (Biller et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, it was shown that, for the hyperthermophilic Thermotogae , similarity of environment is more important for gene exchanges than the geographical proximity (Nesbø et al ., ). The authors compared 11 Thermotoga maritima ‐like genomes, isolated from two environment types (oil reservoirs and marine sites).…”
Section: Discussionmentioning
confidence: 97%
“…The authors compared 11 Thermotoga maritima ‐like genomes, isolated from two environment types (oil reservoirs and marine sites). They reported that the ‘ genomes from the same type of environment tended to be more similar, and exchanged more genes with each other than with geographically close isolates from different types of environments’ (Nesbø et al ., ). One likely vector for such exchanges could be viruses.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the archaeon Pyrococcus abyssi has a highly efficient DNA repair system that continuously repairs temperatureinduced DNA damage (Jolivet et al 2003). Very high levels of homologous recombination are observed in hyperthermophilic Thermotoga spp., where the ratio of nucleotide changes introduced by recombination relative to point mutation (r/m) is in the range 24-100 for genomes originating from geographically distant sites (Nesbø et al 2006a(Nesbø et al , 2015. This is in the upper range of values reported in a comparison of r/m across a large sample of mostly mesophilic Bacteria and Archaea (0.02-64), where values above 10 were interpreted as very high (Vos and Didelot 2009).…”
Section: Nucleic Acids: a Challenge To Keep The Strands Togethermentioning
confidence: 90%